Nek5000/RS performance on advanced GPU architectures - Min, Misun; Lan, Yu-Hsiang; Fischer, Paul; Rathnayake, Thilina; Holmen, John (Frontiers in High Performance Computing, 2025)
The authors explore performance scalability of the open-source thermal-fluids code, NekRS, on the U.S. Department of Energy's leadership computers, Crusher, Frontier, Summit, Perlmutter, and Polaris. Particular attention is given to analyzing performance and time-to-solution at the strong-scale limit for a target efficiency of 80%, which is typical for production runs on the DOE's high-performance computing systems. Several examples of anomalous behavior are also discussed and analyzed.